Structure of preantral follicles, oxidative status and developmental competence of in vitro matured oocytes after ovary storage at 4 °C in the domestic cat model - Anna Rita Piras; Giovanni Pietro Burrai; Federica Ariu; Laura Falchi; Maria Teresa Zedda; Salvatore Pau; Sergio Domenico Gadau; Elisabetta Antuofermo; Daniela Bebbere; Sergio Ledda; Luisa Bogliolo (BMC, 2018)
Abstract Background Storage conditions during transportation of explanted ovaries are a critical step in setting up fertility preservation protocols in both animal and human fields. Here, we evaluated the effects of ovary storage at 4 °C on the preservation of preantral follicles and oocytes retrieved from antral follicles using the domestic cat as model. Methods Ovaries were harvested from fifty-five healthy domestic queens during ovariectomy and stored at 4 °C for 0 (control), 24, 48, 72 and 96 h. In Experiment 1, the effects of the storage period at 4 °C on the morphology, cytoskeleton (α/β tubulin) and DNA integrity (phosphorylation of histone H2AX) of preantral follicles were investigated. In Experiment 2, oocytes recovered from antral follicles were matured and fertilized in vitro to evaluate their meiotic and developmental competence. Reactive oxygen species (ROS), glutathione (GSH) and lipid peroxidation were measured in matured oocytes. Results The results showed that: a) storage up to 24 h did not affect the morphology and the DNA integrity of preantral follicles; b) extended storage times caused progressive morphological abnormalities, disassembling of microtubules and DNA damage; c) storage up to 48 h did not influence in vitro meiotic maturation of oocytes nor cleavage after in vitro fertilization. However, only oocytes stored within the ovary for 24 h produced blastocysts in a percentage similar to control oocytes; d) GSH levels of in vitro matured oocytes did not change at any time during ovary storage; a progressive increase in ROS levels was detected from 48 h associated with elevated lipid peroxidation at 72 and 96 h of storage. Conclusions Storage of cat ovaries for up to 24 h caused minimal alteration of preantral follicles and oocytes. The extension of the storage period beyond 24 h progressively impaired the structure of follicles, and modified the oxidative status of in vitro matured oocytes and their developmental competence after in vitro fertilization. This information may help when setting up programs for fertility conservation, especially for wild feline species which die in geographic areas located far away from ARTs centers.